Identification of cellular targets for specific therapies in neurodevelopmental disorders - Vaz, Ana Rita Mendonça, 1984- (2011)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2010